2012
DOI: 10.1590/s0100-06832012000300031
|View full text |Cite
|
Sign up to set email alerts
|

Duration-frequency relationships of heavy rainfall in Santa Catarina, Brazil

Abstract: suMMary the purpose of this study was to adjust equations that establish relationships between rainfall events with different duration and data from weather stations in the state of santa catarina, Brazil. in this study, the relationships between different duration heavy rainfalls from 13 weather stations of santa catarina were analyzed. From series of maximum annual rainfalls, and using the Gumbel-chow distribution, the maximum rainfall for durations between 5 min and 24 h were estimated considering return pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…These relationships are commonly denominated intensity-duration-frequency (IDF) curves, one of the most widely used methodologies in rainfall-flow transformation processes (Damé et al 2008). Intense rainfall is determined by empirical adjustments of IDF equation parameters, derived from rainfall data for each of the stations (Santos et al 2009, Back et al 2012. The parameters of the intense rainfall equation can be obtained via nonlinear multiple regression, based on information extracted from the series of rainfall data (Campos et al 2014), which do not always contain duration, but are composed of daily records.…”
Section: Palavras-chavementioning
confidence: 99%
“…These relationships are commonly denominated intensity-duration-frequency (IDF) curves, one of the most widely used methodologies in rainfall-flow transformation processes (Damé et al 2008). Intense rainfall is determined by empirical adjustments of IDF equation parameters, derived from rainfall data for each of the stations (Santos et al 2009, Back et al 2012. The parameters of the intense rainfall equation can be obtained via nonlinear multiple regression, based on information extracted from the series of rainfall data (Campos et al 2014), which do not always contain duration, but are composed of daily records.…”
Section: Palavras-chavementioning
confidence: 99%
“…Papalexiou and Koutsoyiannis (2013) fitted GEV in approximately 15,000 series of annual daily maximum rainfall spread across the globe and pointed out that heavy upper tails should be preferred instead of moderate and light. In Brazil, it is very common to use the Gumbel distribution, one of the possible forms of GEV, with moderate upper tail (Back, 2010;Back et al, 2012;Dorneles et al, 2019;Garcia et al, 2011;Martins et al, 2013;Silva and Araújo, 2013). Quadros et al (2011) performed rainfall frequency analysis for different durations in the city of Cascavel (state of Paraná, Brazil) and observed that Gumbel underestimates GEV for large return periods.…”
Section: Introductionmentioning
confidence: 99%
“…Agríc. Ambiental, v.18, n.7, p.727-734, 2014. determinação de estruturas de contenção do processo erosivo (Martins et al, 2010) além de possibilitar o dimensionamento de estruturas hidráulicas para canalização de escoamento superficial, dentre outras utilizações (Genovez & Zuffo, 2000;Rodrigues et al, 2008;Santos et al, 2010;Back et al, 2012;Elsebaie, 2012); contudo, para o desenvolvimento das equações IDF, normalmente é necessário dispor de uma grande base de dados pluviográficos que, na maioria das vezes, não estão acessíveis devido à inexistência de uma rede contínua de monitoramento ou de um número reduzido de informações disponíveis, como é o caso da região em estudo.…”
unclassified